System of phraseological means of implementing the symbolic meanings of the somatonym «hand» in the Russian language - A. B. Ivanova (Вестник Самарского университета: История, педагогика, филология, 2025)
The study is devoted to the analysis of the mechanisms of realization of the symbolic meanings of the lexeme hand in Russian phraseological units. The aim of the study is to identify the set of data of phraseological means and their systematization; determination of the meanings, images and models that form their basis, description of their systemic organization. The material for the study was 164 phraseological units with the lexeme hand, as well as with such names of parts of the hand as shoulder, elbow, fist, finger, little finger, nail, obtained as a result of a continuous sample from modern phraseological dictionaries of the Russian language. In the course of the study, elements of component, cognitive and quantitative methods, as well as semantic and semiotic analysis were used. The considered phraseological units were classified on the basis of the symbolic meanings of the component hand realized in them into seven main semantic groups: activity, work; power, control; physical impact, aggression; agreement, trust, friendliness; help, support, emotional state; measurement of a parameter, quality. As a result of the analysis, it turned out that the studied layer of Russian phraseology has a complex systemic organization: within each group of the considered linguistic means, a ramified system of semantic oppositions was discovered and described, as well as additional components of meanings. The main mechanism for implementing the symbolic meanings of the hand in the studied phraseological units is metonymy, or more precisely, synecdoche – likening a part (hand) to the whole (person), as well as metaphor, personification, comparison of the somatic (corporeal) and other cultural codes: anthropic, spatial